Vector bundles over noncommutative nodal curves - Drozd, Y.A.; Voloshyn, D.E. (Український математичний журнал, 2012)
We describe vector bundles over a class of noncommutative curves, namely, over noncommutative nodal curves of string type and of almost string type. We also prove that, in other cases, the classification of vector bundles over a noncommutative curve is a wild problem. Описано векторнi розшарування над деяким класом некомутативних кривих, а саме, над нодальними некомутативними кривими струнного та майже струнного типу. Встановлено також, що в iнших випадках класифiкацiя векторних розшарувань над некомутативною кривою є дикою задачею.